Effect of Water Restriction and Rehydration on HaematoBiochemical, Enzymatic and Hormonal Activity of Hoggets during Summer Season - Patel, Nitin R.; Modi, Rakesh J.; Islam, Manzarul; Wadhwani, Kishan N. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Present experiment was conducted with the objective to study the effect of water restriction and rehydration on haemato-biochemical,hormonal and enzymatic activity of indigenous sheep under intensive production system. Eighteen farm born unshorn hoggets (25-30kg) of Patanwadi and Marwari breeds were randomly distributed in to three treatment groups on the basis of body weight comprisingof six in each group viz., T1 Control (ad libitum water), T2 (20% water restriction) and T3 (40% water restriction). The experiment wasconducted in summer season for 30 days i.e. 28 days of water restriction and 2 days of rehydration phase. The feed, in accordance withphysiological and production needs of the animals, was offered twice a day (09:00 and 18:00 hrs). Water intake was recorded thrice a day(09:00, 14:00 and 19:00 hrs) and blood samplings was done on day 0, day 28 and after 48 hrs of rehydration. The values of haemoglobin,were significantly decreased, while, serum urea, uric acid, alkaline phosphatase, creatinine phosphokinase, cortisol, triiodothyronine andaldosterone were significantly (p
Keywords: Blood profile; Hogget; Rehydration; Summer; Water restriction